(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Leachables are chemical substances that migrate from pharmaceutical packaging materials into drug products, potentially affecting their stability, quality, efficacy, and patient safety. The present study aimed to evaluate the occurrence of packaging-derived leachables and the degradation behavior of amoxicillin oral suspension during storage under different conditions. The samples were analyzed for physicochemical parameters including pH, drug content, structural or molecular changes, and the presence of potential leachables and degradation products. Amoxicillin, a broad-spectrum β-lactam antibiotic known to undergo hydrolytic degradation in aqueous formulations, was evaluated over a six-week storage period using High-Performance Liquid Chromatography (HPLC), Fourier Transform Infrared (FTIR) Spectroscopy, and Liquid Chromatography–Mass Spectrometry (LC–MS). Six samples were investigated, with three stored under light-protected conditions and three maintained under ambient laboratory lighting throughout the study period. The results demonstrated a gradual decline in amoxicillin content during storage, with an overall reduction of approximately 12–17% after six weeks. LC–MS analysis indicated the presence of ions corresponding to possible packaging-derived leachables, including Bisphenol A, along with ions suggestive of degradation products such as amoxicilloic acid, a well-recognized hydrolytic degradation product of amoxicillin. FTIR analysis revealed minor peak shifts and variations in spectral patterns, indicating slight structural modifications during storage. The findings suggest that both packaging materials and storage conditions may influence the stability of amoxicillin oral suspension and highlight the importance of monitoring packaging-derived leachables and degradation products to ensure the quality, safety, and therapeutic effectiveness of pharmaceutical liquid formulations.